2015
DOI: 10.1002/jor.22933
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐implant stress correlates with bone and cement morphology: Micro‐FE modeling of implanted cadaveric glenoids

Abstract: Aseptic loosening of cemented joint replacements is a complex biological and mechanical process, and remains a clinical concern especially in patients with poor bone quality. Utilizing high resolution finite element analysis of a series of implanted cadaver glenoids, the objective of this study was to quantify relationships between construct morphology and resulting mechanical stresses in cement and trabeculae. Eight glenoid cadavers were implanted with a cemented central peg implant. Specimens were imaged by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…Differences between our results and theirs may be attributable to differences between the studies in loading, implant type (keeled vs. pegged), and image analysis methods. Our finding of failure in trabecular bone immediately surrounding cement mantles is in general agreement with a recent micro‐finite element modeling study from our lab which showed high stresses in these regions …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Differences between our results and theirs may be attributable to differences between the studies in loading, implant type (keeled vs. pegged), and image analysis methods. Our finding of failure in trabecular bone immediately surrounding cement mantles is in general agreement with a recent micro‐finite element modeling study from our lab which showed high stresses in these regions …”
Section: Discussionsupporting
confidence: 92%
“…Our finding of failure in trabecular bone immediately surrounding cement mantles is in general agreement with a recent micro-finite element modeling study from our lab which showed high stresses in these regions. 19 Most previous studies of glenoid loosening used rigid synthetic bone substitute for pragmatic considerations, and did not directly assess the internal implant-cementbone structure. 12,14,16 The purpose of those studies was generally to assess gross loosening for particular component designs, not to identify the mechanisms of loosening.…”
Section: Discussionmentioning
confidence: 99%
“…For studies of implant biomechanics, the overall size of specimens (which influences model size) in the experiments and the numerical models need to be large enough to accommodate the implants. Wee et al [24] explored a multi-scale modeling method that passed the results from macroscale models with no micro-scale trabecular structures to the micro-scale models with voxel-based micro trabecular structures by prescribed boundary conditions. The method was effective yet cumbersome.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the volume of cement in the trabecular bone was recommended for maximizing the interface strength and reducing the incidence of interface failure. Larger cement volumes and contact between cement and cortex are both strongly negatively correlated with high trabecular bone stresses surrounding the cement and may provide a stronger support of cement mantle [ 32 ]. A large average interdigitation and contact area in trabecular bone can be achieved by preparing the bone with pulsatile lavage to allow for cement infiltration, but will be more difficult to achieve in the cortical bone.…”
Section: Discussionmentioning
confidence: 99%